Students' Speaking Skill toward Vocabulary, Grammar, and Self-actualization (A Correlation Study at Seventh Grade of SMP N 5 Tanjungpinang) - Nada Agustiana (Juliet, 2020)
This research discussed the correlation of students’ speaking skill toward vocabulary, grammar, and self-actualization. The goal of this research was to find out whether or not there is a correlation of students’ speaking skill toward vocabulary, grammar, and self-actualization. The populations of the research were 221 students and 36 students were being the sample of the research. All was from the seventh grade of SMP N 5 Tanjungpinang in the academic year of 2018/2019. The sample was taken by cluster random sampling. This research was used correlation study by collecting the data from the multiple choices, oral test and questionnaire. The researcher used SPSS version 22.00 to calculate the data. The result demonstrated that the data of this research was normal, homogeny and linear. There was positive correlation of each variable. Based on the data analysis computed by using application, it was obtained that the number of r is 0.890. It showed there was very strong correlation of students’ speaking skill toward vocabulary, grammar, and self-actualization. From the f-test, the result showed the value of fobserved> ftable, it means Ha was accepted. Therefore, there was a significant correlation of students' speaking skill toward vocabulary, grammar, and self-actualization text at the seventh grade of SMP N 5 Tanjungpinang in the academic year of 2018/2019..